A catalyst carrier for propane dehydrogenation and its preparation method and application
By using M1-M2-Al-O composite oxide and γ-Al2O3 as support, a highly active and stable propane dehydrogenation catalyst was prepared, which solved the serious problem of existing catalysts in the high temperature and achieved high efficiency Propane conversion and stability improve.
Patent Information
- Application Number
- CN201910912208.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-09-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-09-25
AI Technical Summary
The existing propane dehydrogenation catalysts are used at high temperatures, resulting in serious carbon accumulation in the catalyst and insufficient activity and stability. In particular, there are environmental problems with chromium catalysts, and there is limited room for improving the activity and stability of platinum catalysts.
M1-M2-Al-O composite oxide and γ-Al2O3 were used as catalyst support to prepare the catalyst by particle screening doping and additive extrusion molding, optimize the acid center on the surface of the support, and improve the activity and stability of the catalyst.
The high activity and stability of the propane dehydrogenation catalyst are achieved, the propane conversion rate is more than 41%, the single-way stability is high, and the catalyst carbon deposit is reduced.
Smart Images

Figure BDA0002215068930000201 
Figure BDA0002215068930000212
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst carrier for propane dehydrogenation and a preparation method and application thereof. Background Art
[0002] Propylene is a colorless, non-irritating gas with a slightly sweet taste at room temperature. It is a very important organic chemical raw material. Together with isobutylene and ethylene, it is considered the basis of modern petrochemical industry. The traditional source of propylene is the by-product of steam cracking and catalytic cracking. In recent years, the market demand for propylene has continued to increase, and its demand growth has exceeded that of ethylene. In the next few years, the gap between the two will become larger and larger. Therefore, countries around the world have been committed to developing new routes for the preparation of propylene, such as methanol to olefins (MTO), methanol to propylene (MTP) and alkane dehydrogenation to produce propylene (PDH). Among them, the method of preparing the corresponding propylene using propane as raw material through direct dehydrogenation process has received increasing attention.
[0003] Due to the limitation of thermodynamic factors, the propane dehydrogenation catalytic reaction is carried out at a relatively high temperature. The serious carbon deposition of the catalyst leads to the deactivation of the catalyst. The development of catalysts with high activity, high selectivity and high stability has become the key to propane dehydrogenation technology. At present, commercial dehydrogenation catalysts are mainly divided into two categories: chromium and platinum. Cr2O3 / Al2O3 catalyst is the most widely used chromium catalyst. The three processes of CATOFIN, PDH and FDB all use chromium catalysts. At present, environmental protection issues are receiving more and more attention and are the biggest problem facing chromium catalysts. Platinum catalysts have good catalytic dehydrogenation performance and are pollution-free to the environment. The OLEFLEX process uses Pt / Al2O3 catalysts. At present, the main hot spots and difficulties in olefin production research are how to improve the activity and stability of platinum catalysts.
[0004] Duan et al. published "Effect of Sodium Addition to PtSn / AlSBA-15 on the Catalytic Properties in Propane Dehydrogenation" in Catalysis Letters, 2011, 141(1): 120-127. They found that the addition of alkali metal sodium can neutralize some of the strong acid on the catalyst surface, thereby reducing carbon deposition. Among them, PtSnNa (1.0%) / AlSBA-15 has better performance, which can be attributed to the strong interaction between its highly dispersed Pt and the carrier. However, excessive Na can cause Sn to precipitate and form an alloy phase with Pt, which will lead to reduced catalytic performance.
[0005] Great progress has been made in propane dehydrogenation catalysts, but there is still room for improvement in catalyst activity. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the first aspect of the present invention provides a catalyst carrier for propane dehydrogenation, wherein the carrier includes M1-M2-Al-O composite oxide and γ-Al2O3, which can effectively improve the acid center on the surface of the carrier and improve the activity and stability of the catalyst.
[0007] The second aspect of the present invention provides a method for preparing the above catalyst carrier.
[0008] A third aspect of the present invention provides a catalyst for dehydrogenating propane to propylene.
[0009] A fourth aspect of the present invention provides a method for preparing a catalyst for dehydrogenating propane to propylene.
[0010] A fifth aspect of the present invention provides a method for producing propylene by dehydrogenating propane.
[0011] According to the first aspect of the present invention, the catalyst carrier comprises M1-M2-Al-O composite oxide and γ-Al2O3, M1 is selected from Group IIB elements, and M2 is selected from Group VIII elements.
[0012] According to some embodiments of the present invention, the mass ratio of the M1-M2-Al-O composite oxide and γ-Al2O3 is (4-99):1, for example, 4, 6, 8, 10, 12, 14, 16, 18, 19, 20, 30, 40, 50, 70, 90 and any value therebetween.
[0013] According to some embodiments of the present invention, the mass ratio of the M1-M2-Al-O composite oxide and γ-Al2O3 is (5-40):1.
[0014] According to some embodiments of the present invention, the mass ratio of the M1-M2-Al-O composite oxide and γ-Al2O3 is (6-19):1.
[0015] When the mass ratio of M1-M2-Al-O composite oxide and γ-Al2O3 is within the above-mentioned specific range, the advantages of the two carriers can be taken into account. When the mass ratio of M1-M2-Al-O composite oxide and γ-Al2O3 is too low, the interaction between Pt and the carrier is weakened, which is not conducive to the dispersion of Pt. At the same time, the acidity of the catalyst is enhanced, the by-products increase, carbon deposition is easy, and it is not conducive to stability. When the mass ratio of M1-M2-Al-O composite oxide and γ-Al2O3 is too high, the specific surface area of the catalyst is reduced, which is not conducive to the dispersion of Pt, and the strength is also reduced.
[0016] According to some embodiments of the present invention, in the composite oxide M1-M2-Al-O, in terms of molar ratio, Al:M1 is (1-1.99):1, and Al:M2 is (1-199):1.
[0017] According to some embodiments of the present invention, the IIB element is selected from one or more of Zn and Cd, and the VIII element is selected from one or more of Fe, Co and Ni.
[0018] The mixed carrier of M1-M2-Al-O composite oxide and γ-Al2O3 provided by the present invention combines the advantages of the two carriers and can obtain higher activity, stability and strength.
[0019] According to a second aspect of the present invention, the method for preparing the above-mentioned catalyst carrier comprises mixing the M1-M2-Al-O composite oxide and γ-Al2O3, and then forming the mixture after adding an auxiliary agent.
[0020] According to some embodiments of the present invention, the method for preparing the carrier comprises the following steps:
[0021] a) doping and mixing M1-M2-Al-O composite oxide and γ-Al2O3 to obtain a mixed material a1;
[0022] b) adding an auxiliary agent to the mixture a1 and performing extrusion molding to obtain a molded product;
[0023] c) drying and calcining the shaped product to obtain the catalyst support.
[0024] According to some embodiments of the present invention, the particle size of the M1-M2-Al-O composite oxide is 50-120 μm, for example, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm and any value therebetween.
[0025] According to some embodiments of the present invention, the particle size of the M1-M2-Al-O composite oxide is 60-90 μm.
[0026] According to some embodiments of the present invention, the particle size of the Al2O3 is 5-40 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm and any value therebetween.
[0027] According to some embodiments of the present invention, the particle size of the Al2O3 is 10-30 μm.
[0028] According to some embodiments of the present invention, the auxiliary agent includes sesbania powder, polyethylene glycol, inorganic acid and water.
[0029] According to some embodiments of the present invention, the polyethylene glycol comprises a first polyethylene glycol and a second polyethylene glycol, wherein the average molecular weight of the first polyethylene glycol is 4000-8000, and the average molecular weight of the second polyethylene glycol is 400-1000.
[0030] According to some embodiments of the present invention, the mass of the sesbania powder is 2-4% based on the total weight of the carrier.
[0031] According to some embodiments of the present invention, based on the total weight of the carrier, the mass of the first polyethylene glycol is 1-3%.
[0032] According to some embodiments of the present invention, based on the total weight of the carrier, the mass of the second polyethylene glycol is 0.2-0.4%.
[0033] According to some embodiments of the present invention, the mass of the inorganic acid is 4-6% based on the total weight of the carrier.
[0034] According to some embodiments of the present invention, the mass of the water is 20-40% based on the total weight of the carrier.
[0035] According to some embodiments of the present invention, the mass ratio of the sesbania powder: the first polyethylene glycol: the second polyethylene glycol: the inorganic acid: the water is 2-4: 1-3: 0.2-0.4: 4-6: 30.
[0036] According to some embodiments of the present invention, the inorganic acid is selected from one or more of nitric acid, sulfuric acid, hydrochloric acid and hydrofluoric acid.
[0037] According to some embodiments of the present invention, step b) comprises the following steps:
[0038] b1) adding sesbania powder and the first polyethylene glycol to the mixture a1 and mixing them to obtain an intermediate mixture;
[0039] b2) adding a mixture of a second polyethylene glycol, an inorganic acid and water to the intermediate mixture of step b1) for extrusion molding to obtain a molded product; the molded product has a diameter of 2-5 mm and a length of 0.5-3 cm.
[0040] In some preferred embodiments of the present invention, step b) includes the following steps: first, adding sesbania powder and a first polyethylene glycol (e.g., polyethylene glycol-6000) to M1-M2-Al-O and γ-Al2O3 and mixing for 20 to 30 minutes, then slowly adding a mixture of a second polyethylene glycol (e.g., polyethylene glycol-600), nitric acid and water and kneading until a sticky dough is formed, and extruding the sticky dough into strips, wherein the molded strips preferably have a diameter of 3 mm and a length of 1 cm.
[0041] According to some embodiments of the present invention, in step c), the calcination temperature is 450° C.-650° C., and the calcination time is 6-24 hours.
[0042] According to some embodiments of the present invention, the doping and mixing described in step a) includes crushing and screening the M1-M2-Al-O particles into 60-100 μm, and doping and mixing them with 10-40 μm γ-Al2O3 in a kneader for 20-40 minutes.
[0043] According to some embodiments of the present invention, after the second polyethylene glycol, nitric acid and water are mixed, the conductivity measured at 20° C. is 0.45-0.60 S / cm.
[0044] The mixed carrier provided by the present invention adopts the method of particle screening and doping + auxiliary agent extrusion molding, which is beneficial to improving the strength and specific surface area of the catalyst and is also beneficial to the molding process.
[0045] According to the third aspect of the present invention, the catalyst comprises, in parts by weight, 0.1-10 parts of Pt and / or its oxide; 0.1-10 parts of Sn and / or its oxide; 0.1-10 parts of alkali metals and / or alkali metal oxides; and 75-99.7 parts of M1-M2-Al-O composite oxide and γ-Al2O3 mixed carrier.
[0046] According to some embodiments of the present invention, the catalyst includes, by weight, 0.1-5 parts of Pt and / or its oxide; 0.1-5 parts of Sn and / or its oxide; 0.1-5 parts of alkali metals and / or alkali metal oxides; and 85-99 parts of M1-M2-Al-O composite oxide and γ-Al2O3 mixed carrier.
[0047] According to some embodiments of the present invention, the catalyst includes, by weight, 0.1-1.5 parts of Pt and / or its oxide; 0.1-1.5 parts of Sn and / or its oxide; 0.1-2 parts of alkali metals and / or alkali metal oxides; and 90-99 parts of M1-M2-Al-O composite oxide and γ-Al2O3 mixed carrier.
[0048] According to a fourth aspect of the present invention, the method for preparing the above catalyst comprises the following steps:
[0049] (I) obtaining an impregnation solution A, wherein the impregnation solution A comprises a tin salt;
[0050] (II) mixing the M1-M2-Al-O composite oxide and the γ-Al2O3 mixed carrier with the impregnation solution A, drying and calcining to obtain a catalyst precursor;
[0051] (III) obtaining an impregnation solution B, wherein the impregnation solution B comprises a platinum salt and the pH value of the impregnation solution is 1-5, preferably 1-4;
[0052] (IV) The catalyst precursor is mixed with the impregnation solution 2, dried and calcined to obtain the catalyst.
[0053] According to some embodiments of the present invention, the impregnation solution A is a hydrochloric acid solution containing a soluble salt of Sn.
[0054] According to some embodiments of the present invention, the tin salt is selected from one or more of tin nitrate, stannous chloride, tin tetrachloride, tin sulfate and tin acetate.
[0055] According to some embodiments of the present invention, the platinum salt is selected from one or more of chloroplatinic acid, platinum chloride, platinum nitrate and platinum sulfate.
[0056] According to some embodiments of the present invention, the mixing temperature in step (II) is 10-80°C, the mixing time is 1-24 hours, the drying temperature is 80°C-150°C, the drying time is 6-24 hours, the roasting temperature is 450°C-650°C, and the roasting time is 6-24 hours.
[0057] According to some embodiments of the present invention, the mixing temperature in step (IV) is 10-80°C, the mixing time is 1-24 hours, the drying temperature is 80°C-150°C, the drying time is 6-24 hours, the roasting temperature is 450°C-650°C, and the roasting time is 6-24 hours.
[0058] According to some embodiments of the present invention, the catalyst carrier has a molding strength of 150-250 N / cm and a specific surface area of 70-120 m 2 / g.
[0059] According to some embodiments of the present invention, the catalyst carrier has a molding strength of 180-240 N / cm and a specific surface area of 80-120 m 2 / g.
[0060] In the present invention, M1-M2-Al-O only means that the oxide contains four elements M1, M2, Al and O, and does not constitute a limitation on the ratio between M1, M2, Al and O.
[0061] According to a fifth aspect of the present invention, the method for preparing propylene by dehydrogenating propane comprises introducing a raw material containing propane to react in the presence of the above catalyst or the catalyst prepared by the above method.
[0062] According to some embodiments of the present invention, the volume ratio of water vapor to propane in the raw material containing propane is (10-1):1.
[0063] According to some embodiments of the present invention, the volume ratio of water vapor to propane is (6-2):1.
[0064] According to some embodiments of the present invention, the reaction temperature is 400°C-600°C, the reaction pressure is 0-1MPa, and the mass space velocity of propane is 3.0-8.0h -1 .
[0065] According to some embodiments of the present invention, the reaction pressure is 0.01 MPa to 0.5 MPa, and the propane space velocity is 3.5-6.5 h -1 .
[0066] The single Al2O3 carrier has high acidity, which is not conducive to the stability of the catalyst. The composite oxide M1-M2-Al-O and γ-Al2O3 mixed carrier provided by the present invention, M1 is selected from the IIB group elements, M2 is selected from the VIII group elements, and the mixed carrier is prepared by particle screening doping + auxiliary agent extrusion molding. The catalyst is used for propane dehydrogenation reaction, and the propane conversion rate reaches more than 41%, and the single-pass stability is high. DETAILED DESCRIPTION
[0067] The present invention is further described below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention.
[0068] [Example 1]
[0069] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0070] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0071] [Example 2]
[0072] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 200g of 80μm particles, which were mixed with 100g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0073] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0074] [Example 3]
[0075] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 240g of 80μm particles, which were mixed with 60g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0076] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0077] [Example 4]
[0078] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 258g of 80μm particles, which were mixed with 42g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0079] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0080] [Example 5]
[0081] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 280g of 80μm particles, which were mixed with 20g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0082] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0083] [Example 6]
[0084] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 285g of 80μm particles, which were mixed with 15g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0085] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0086] [Example 7]
[0087] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 290g of 80μm particles, which were mixed with 10g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0088] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0089] [Example 8]
[0090] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 297g of 80μm particles, which were mixed with 3g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0091] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0092] [Example 9]
[0093] CdFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0094] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0095] [Example 10]
[0096] ZnCo 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0097] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0098] [Example 11]
[0099] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 50μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0100] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0101] [Example 12]
[0102] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 120μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0103] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0104] [Example 13]
[0105] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 5μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0106] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0107] [Example 14]
[0108] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 50μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0109] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0110] [Example 15]
[0111] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm α-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0112] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0113] [Example 16]
[0114] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm β-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0115] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0116] [Example 17]
[0117] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-6000, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.50S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0118] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0119] [Example 18]
[0120] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-600 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0121] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0122] [Example 19]
[0123] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0124] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix well, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.174g of sodium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix well, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0125] [Example 20]
[0126] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0127] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix well, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.302g of rubidium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix well, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0128] [Comparative Example 1]
[0129] The ZnAl2O4 composite oxide was crushed and screened into 300g of 80μm particles, and then 9g of sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips, preferably with a diameter of 3mm and a length of 1cm. The formed strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1. Weigh 9.88g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30°C for 12 hours, and then dry at 100°C for 16 hours to obtain a catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and dissolve it in 10mL of water, adjust the pH value to 3.0, add it to I under stirring, mix evenly, soak at 30°C for 12 hours, dry at 100°C for 16 hours, and calcine in a muffle furnace at 600°C for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation is the same as in Example 1, and the results are shown in Table 2.
[0130] [Comparative Example 2]
[0131] ZnFe 0.2 Al 1.8 The O4 composite oxide was crushed and screened into 80 μm particles. 300 g was mixed in a kneader for 30 minutes, and then 9 g of sesbania powder and 6 g of polyethylene glycol-6000 were added and mixed for 25 minutes to obtain a mixture. Then, a mixture of 0.9 g of polyethylene glycol-600, 15 g of nitric acid and 90 g of water was mixed, and the conductivity was measured at 20°C to be 0.52 S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3 mm and a length of 1 cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0132] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0133] [Comparative Example 3]
[0134] 300g of 20μm γ-Al2O3 particles were mixed in a kneader for 30min, and then 9g of sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips, preferably with a diameter of 3mm and a length of 1cm. The formed strips were dried at 100°C for 16 hours, and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0135] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.080g of chloroplatinic acid hexahydrate and 0.207g of potassium nitrate and dissolve them in 10mL of water, adjust the pH value to 3.0, add them to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor to propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0136] [Comparative Example 4]
[0137] ZnFe 0.2 Al 1.8The O4 composite oxide was crushed and screened into 270g of 80μm particles, which were mixed with 30g of 20μm γ-Al2O3 particles in a kneader for 30min, and then 9g of field sesbania powder and 6g of polyethylene glycol-6000 were added and mixed for 25min to obtain a mixture. Then, a mixture of 0.9g of polyethylene glycol-600, 15g of nitric acid and 90g of water was mixed, and the conductivity was measured at 20°C to be 0.52S / cm. The mixed solution was slowly added to the mixture and kneaded until a sticky mass was formed, and the sticky mass was extruded into strips with a preferred diameter of 3mm and a length of 1cm. The molded strips were dried at 100°C for 16 hours and calcined in a muffle furnace at 600°C for 20 hours to obtain a carrier. The carrier composition and properties are shown in Table 1.
[0138] Weigh 9.80g of the carrier into a beaker, then weigh 0.171g of stannous chloride dihydrate and dissolve it in 10mL of hydrochloric acid solution, add the above carrier under stirring, mix evenly, soak at 30℃ for 12 hours, and then dry at 100℃ for 16 hours to obtain the catalyst precursor, which is recorded as I. Weigh 0.151g of chloroplatinic acid hexahydrate and dissolve it in 10mL of water, adjust the pH value to 3.0, add it to I under stirring, mix evenly, soak at 30℃ for 12 hours, dry at 100℃ for 16 hours, and calcine in a muffle furnace at 600℃ for 20 hours to obtain a propane dehydrogenation catalyst. The catalyst evaluation conditions are as follows: 0.5g of catalyst is loaded into the above isothermal fixed bed reactor (catalyst bed height 17mm), the reaction is at normal pressure and the temperature is 550℃; the volume ratio of water vapor and propane is 2:1; the propane mass space velocity is 5.0h -1 , the results are shown in Table 2.
[0139] Table 1
[0140]
[0141]
[0142] Table 2
[0143]
[0144]
[0145] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A catalyst carrier for propane dehydrogenation, comprising a M1-M2-Al-O composite oxide and γ-Al2O3, wherein M1 is selected from Group IIB elements, and M2 is selected from Group VIII elements; the Group IIB elements are selected from one or more of Zn and Cd, and the Group VIII elements are selected from one or more of Fe, Co and Ni; the mass ratio of the M1-M2-Al-O composite oxide and γ-Al2O3 is (4-99):1; in the composite oxide M1-M2-Al-O, in terms of molar ratio, Al:M1 is (1-1.99):1, and Al:M2 is (1-199):1; the particle size of the M1-M2-Al-O composite oxide is 50-120 μm, and the particle size of the γ-Al2O3 is 5-40 μm.
2. The catalyst carrier according to claim 1, characterized in that The mass ratio of the M1-M2-Al-O composite oxide and γ-Al2O3 is (5-40):
1.
3. The catalyst carrier according to claim 2, characterized in that The mass ratio of the M1-M2-Al-O composite oxide and γ-Al2O3 is (6-19):
1.
4. A method for preparing the catalyst carrier according to any one of claims 1 to 3, comprising mixing the M1-M2-Al-O composite oxide and γ-Al2O3, adding an auxiliary agent and then molding.
5. The method for preparing a catalyst carrier according to claim 4, characterized in that: The following steps are involved: a) doping and mixing M1-M2-Al-O composite oxide and γ-Al2O3 to obtain a mixed material a1; b) adding an auxiliary agent to the mixture a1 and performing extrusion molding to obtain a molded product; c) drying and calcining the shaped product to obtain the catalyst support.
6. The method for preparing a catalyst carrier according to claim 5, characterized in that: The auxiliary agent comprises sesbania powder, polyethylene glycol, inorganic acid and water, And / or, the inorganic acid is selected from one or more of nitric acid, sulfuric acid, hydrochloric acid and hydrofluoric acid.
7. The method for preparing a catalyst carrier according to claim 6, characterized in that: The particle size of the M1-M2-Al-O composite oxide is 60-90 μm.
8. The method for preparing a catalyst carrier according to claim 7, characterized in that: The particle size of the γ-Al2O3 is 10-30 μm.
9. The method for preparing a catalyst carrier according to claim 8, characterized in that: The polyethylene glycol comprises a first polyethylene glycol and a second polyethylene glycol, wherein the average molecular weight of the first polyethylene glycol is 4000-8000, and the average molecular weight of the second polyethylene glycol is 400-1000.
10. The method for preparing a catalyst carrier according to claim 9, characterized in that: Based on the total weight of the carrier, the mass of the sesbania powder is 2-4%, the mass of the first polyethylene glycol is 1-3%, the mass of the first polyethylene glycol is 0.2-0.4%, the mass of the inorganic acid is 4-6%, and the mass of water is 20-40%.
11. The method for preparing a catalyst carrier according to claim 10, characterized in that: The mass ratio of the sesbania powder: the first polyethylene glycol: the second polyethylene glycol: the inorganic acid: water is (2-4): (1-3): (0.2-0.4): (4-6):
30.
12. The method for preparing a catalyst carrier according to any one of claims 4 to 11, characterized in that: The step b) comprises the following steps: b1) adding sesbania powder and the first polyethylene glycol to the mixture a1 and mixing them to obtain an intermediate mixture; b2) adding a mixture of a second polyethylene glycol, an inorganic acid and water to the intermediate mixture of step b1) for extrusion molding to obtain a molded product; the molded product has a diameter of 2-5 mm and a length of 0.5-3 cm; And / or, in step c), the calcination temperature is 450° C.-650° C., and the calcination time is 6-24 hours.
13. A catalyst for dehydrogenating propane to produce propylene, the catalyst comprising, in parts by weight: 0.1-5 parts, Pt and / or its oxide; 0.1-5 parts, Sn and / or its oxide; 0.1-5 parts of alkali metal and / or alkali metal oxide; 75-99.7 parts of a catalyst carrier according to any one of claims 1 to 3 or a catalyst carrier prepared by the method according to any one of claims 4 to 12.
14. The catalyst according to claim 13, characterized in that Contains 0.1-5 parts of Pt and / or its oxide.
15. The catalyst according to claim 14, characterized in that Includes 0.1-1.5 parts of Pt and / or its oxide.
16. The catalyst according to any one of claims 13 to 15, characterized in that Contains 0.1-5 parts of Sn and / or its oxide.
17. The catalyst according to claim 16, characterized in that Includes 0.1-1.5 parts of Sn and / or its oxide.
18. The catalyst according to claim 17, characterized in that It includes 0.1 to 5 parts of alkali metal and / or alkali metal oxide.
19. The catalyst according to claim 18, characterized in that Includes 0.1-2 parts of alkali metal and / or alkali metal oxide.
20. The catalyst according to claim 19, characterized in that Includes 85-99 parts of catalyst carrier.
21. The catalyst according to claim 20, characterized in that Comprises 90-99 parts of catalyst carrier.
22. A method for preparing the catalyst according to any one of claims 13 to 21, comprising the following steps: (I) obtaining an impregnation solution A, wherein the impregnation solution A comprises a tin salt; (II) mixing the catalyst carrier according to any one of claims 1 to 3 or the catalyst carrier prepared by the method according to any one of claims 4 to 12 with the impregnation solution A, drying and calcining to obtain a catalyst precursor; (III) obtaining an impregnation solution B, wherein the impregnation solution B comprises a platinum salt and the pH value of the impregnation solution is 1-5; (IV) The catalyst precursor is mixed with the impregnation solution B, dried and calcined to obtain the catalyst.
23. The method for preparing a catalyst according to claim 22, characterized in that: The pH value of the impregnation solution is 1-4.
24. The method for preparing a catalyst according to claim 22 or 23, characterized in that: The tin salt is selected from one or more of tin nitrate, stannous chloride, tin sulfate and tin acetate; and or, the platinum salt is selected from one or more of chloroplatinic acid, platinum chloride, platinum nitrate and platinum sulfate; and or, The mixing temperature in step (II) and step (IV) is 10-80°C, the mixing time is 1-24 hours, the drying temperature is 80°C-150°C, the drying time is 6-24 hours, the roasting temperature is 450°C-650°C, and the roasting time is 6-24 hours.
25. A method for preparing propylene by dehydrogenating propane, comprising introducing a raw material containing propane to carry out a reaction in the presence of the catalyst according to any one of claims 13 to 21 or the catalyst prepared by the method according to any one of claims 22 to 24.
26. The method according to claim 25, characterized in that The volume ratio of water vapor to propane in the raw material containing propane is (10-1):1; and / or the reaction temperature is 400°C-600°C, the reaction pressure is 0-1MPa, and the mass space velocity of propane is 3.0-8.0h -1 .
Citation Information
Patent Citations
Catalyst for isobutane dehydrogenation production of isobutylene and preparation method thereof
CN106607023A
Dehydrogenation catalyst and preparation method thereof
CN106669792A